The Improving Students’ Pronunciation Using Tongue Twister Technique in TikTok Application - Lulu Nabila; Heryatun, Yayu; Siti Rohbiah, Tatu (English Education, Linguistics, and Literature Journal, 2023)
This research is to investigate the process of Students' English pronunciation in TikTok application for the tenth grade students’ of MA Negeri 2 Kota Serang, by using tongue twister technique. The subject of this research involves 60 students’ as sample among tenth class of MA Negeri 2 Kota Serang, year 2021 as population. This study employed a quantitative methodology. Pre-test and post-test techniques were used in this study's quasi-experimental design with two classes, the experimental class and the control class. According to the calculation's findings, t0 had a value of 6,7 and 58 degrees of freedom. In this study, the level of significance for the levels of 5% and 1% was 1,68 for df 58 and 2,4 for df 58, respectively. These values were shown in the table of significance. When comparing students' English pronunciation in the TikTok application with and without the tongue twister technique, the results, when compared to the test's criteria, showed a significant difference. Therefore, tongue twisters are useful and suitable to improving students' English pronunciation in the tenth grade at MA Negeri 2 Kota Serang.